Arbitrated Magazine Management Training. Special International Edition, within the framework of the XVI Anniversary. - López de Castro, Sandra (Revista Arbitrada Formación Gerencial, 2022)
MANAGEMENT MAGAZINE IN ECONOMIC, HUMANISTIC AND TECHNICAL AREAS